English Teachers’ Innovative Approach to Teaching Speaking Skills - Fitriani, Nandita; Rofiq, Annur; Ariani, Musli (English Education:Journal of English Teaching and Research, 2025)
To facilitate students with speaking proficiency that is applicable in today’s real-world communication, an innovative approach to teaching of speaking is needed. The purpose of this research is to investigate what innovative teaching approach that teachers use to teach students English speaking skills that will assist them in real-world communication. This study used a qualitative-descriptive case study design. The data were collected through observations and interviews and analyzed by using thematic analysis. The findings reveal that there are six characteristics of innovative teaching that teachers used when teaching English speaking skills in the classroom. They are teacher-student collaboration, HOTS oriented towards the teaching of speaking, integration of ICT in the teaching of speaking, teaching of speaking that involve 21st-century learning skills, teaching of speaking that strengthen literacy skills, and the teaching of speaking that strengthen character education (SCE). Understanding the innovative teaching of speaking implemented by the teacher as revealed in this study, further studies intended to analyze and deepen the understanding of the impact of these innovative teaching approach on students’ speaking performance should be conducted.